Fall Risk Assessment Predicts Fall‐Related Injury, Hip Fracture, and Head Injury in Older Adults. Issue 11 (30th September 2016) - Nilsson, Martin; Eriksson, Joel; Larsson, Berit; Odén, Anders; Johansson, Helena; Lorentzon, Mattias
Abstract : Objectives: To investigate the role of a fall risk assessment, using the Downton Fall Risk Index (DFRI), in predicting fall‐related injury, fall‐related head injury and hip fracture, and death, in a large cohort of older women and men residing in Sweden. Design: Cross sectional observational study. Setting: Sweden. Participants: Older adults (mean age 82.4 ± 7.8) who had a fall risk assessment using the DFRI at baseline (N = 128, 596). Measurements: Information on all fall‐related injuries, all fall‐related head injuries and hip fractures, and all‐cause mortality was collected from the Swedish Patient Register and Cause of Death Register. The predictive role of DFRI was calculated using Poisson regression models with age, sex, height, weight, and comorbidities as covariates, taking time to outcome or end of study into account. Results: During a median follow‐up of 253 days (interquartile range 90–402 days) (>80, 000 patient‐years), 15, 299 participants had a fall‐related injury, 2, 864 a head injury, and 2, 557 a hip fracture, and 23, 307 died. High fall risk (DFRI ≥3) independently predicted fall‐related injury (hazard ratio (HR) = 1.43, 95% confidence interval (CI) = 1.39–1.49), hip fracture (HR = 1.51, 95% CI =1.38–1.66), head injury (HR = 1.12, 95% CI = 1.03–1.22), and all‐cause mortality (HR = 1.39, 95% CI = 1.35–1.43). DFRI more strongly predicted head injury (HR = 1.29, 95% CI = 1.21–1.36 vs HR = 1.08, 95% CI = 1.04–1.11) and hip fracture (HR = 1.41, 95% CI = 1.30–1.53 vs HR = 1.08, 95% CI = 1.05–1.11) in 70‐year old men than in 90‐year old women ( P < .001). Conclusion: Fall risk assessment using DFRI independently predicts fall‐related injury, fall‐related head injury and hip fracture, and all‐cause mortality in older men and women, indicating its clinical usefulness to identify individuals who would benefit from interventions.